Current collector and preparation method thereof, pole piece, battery and electric device

By introducing a nonwoven fabric layer into the base film of the battery current collector and connecting the conductive film layer with a conductive carbon film layer, the problems of poor binding force and insufficient wetting performance of the existing battery current collector are solved, and the cycling performance of the battery is significantly improved.

CN119852416APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311352416.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The bonding force between the conductive metal film and the current collector of the existing battery current collector is different, which is prone to cracking and mold release, and has poor wetting performance, which affects the cycling performance of the battery.

Method used

The base film includes a nonwoven fabric layer, and the conductive film layer is connected by a conductive carbon film layer, thereby improving the connection firmness between the conductive film layer and the nonwoven fabric, and enhancing the wetting and cycling performance of the current collector.

Benefits of technology

The bonding force between the conductive metal film and the current collector is improved, the probability of cracking and mold release is reduced, and the circulation and wetting performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852416A_ABST
    Figure CN119852416A_ABST
Patent Text Reader

Abstract

The invention discloses a current collector and a preparation method thereof, a pole piece, a battery and an electric device. The current collector comprises a base film, a conductive film layer arranged on at least one side of the base film and a conductive carbon film layer located between the base film and the conductive film layer, and the base film comprises a non-woven fabric layer. The base film comprises the non-woven fabric layer, so that the non-woven fabric layer is connected with the conductive film layer through the conductive carbon film layer, on one hand, the non-woven fabric has a porous structure, the electrolyte wettability of a cell system can be improved, the infiltration time can be shortened, the production effect can be improved, the anode interface problem can be improved, and the cycle performance of the cell can be improved; on the other hand, the conductive carbon film layer is arranged between the non-woven fabric and the conductive film layer, and the conductive film layer is connected to the non-woven fabric through the conductive carbon layer, so that the connection firmness between the conductive film layer and the non-woven fabric is improved, the probability of cracking and demolding is reduced, the gap between the conductive film layer and the non-woven fabric is reduced, and then the contact resistance is reduced; the cycle performance of the battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a current collector and a preparation method thereof, a pole piece, a battery and an electrical device. Background Art

[0002] Battery cells are widely used because of their reliable working performance, no pollution, and no memory effect. For example, as environmental protection issues are increasingly valued and new energy vehicles become more popular, the demand for power battery cells will show explosive growth.

[0003] The positive and negative current collectors of the battery are important components of the battery, as they are carriers of the positive and negative active materials and can conduct electricity during the charging and discharging process. Currently, the current collectors are usually made of copper foil or aluminum foil, and the active material slurry is directly coated on the surface of the copper foil or aluminum foil. However, the current collectors prepared by this method have poor bonding strength between the conductive metal film and the current collector, are prone to cracking and demolding, and have poor wetting performance. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a current collector to improve the bonding force between the conductive metal film and the current collector, reduce cracking, improve the wettability, and thereby improve the cycle performance of the battery.

[0005] In order to achieve the above-mentioned objectives, the embodiments of the present application provide a current collector and a preparation method thereof, a pole piece, a battery and an electrical device.

[0006] In a first aspect, an embodiment of the present application proposes a current collector, comprising a base film, a conductive film layer disposed on at least one side of the base film, and a conductive carbon film layer located between the base film and the conductive film layer, wherein the base film comprises a non-woven fabric layer.

[0007] Therefore, in the technical solution of the embodiment of the present application, the base film includes a non-woven fabric layer, so that the non-woven fabric layer is connected to the conductive film layer through the conductive carbon film layer. On the one hand, the non-woven fabric has a porous structure, which can improve the electrolyte wettability of the battery system, shorten the infiltration time, improve the production effect, improve the anode interface problem, and improve the cycle performance of the battery. On the other hand, by arranging a conductive carbon film layer between the non-woven fabric and the conductive film layer, the conductive film layer is connected to the non-woven fabric through the conductive carbon layer, which improves the connection firmness between the conductive film layer and the non-woven fabric, reduces the probability of cracking and demolding, reduces the gap between the conductive film layer and the non-woven fabric, and thus reduces the contact resistance and improves the cycle performance of the battery.

[0008] It should be noted that in some embodiments of the present application, the conductive carbon film layer may be a conductive film layer partially containing carbon, and in some embodiments of the present application, the conductive carbon film layer may be a conductive film layer containing only carbon, and the present application does not limit this. A conductive carbon film layer is provided on at least one side of the base film, and in some embodiments of the present application, a conductive carbon film layer may be provided on only one side of the base film, and in some embodiments of the present application, a conductive carbon film layer may be provided on both sides of the base film.

[0009] In any embodiment, the conductive carbon film layer includes at least one of a graphite layer or a graphene layer. By using at least one of a graphite layer or a graphene layer, the characteristics of graphite and graphene being easy to deposit and connect on the rough surface of a non-woven fabric can be utilized to improve the firmness of the combination of the graphite layer or the graphene layer with the non-woven fabric layer, reduce the pores of the contact cross section, reduce the risk of falling off, and thus reduce the contact resistance and improve the cycle performance of the battery cell. At the same time, graphite and graphene have good electrical conductivity and can improve the conductivity of the current collector. It should be noted that when the conductive carbon film layer is a graphene layer, due to the good growth performance of graphene and the rough and porous fiber structure of the non-woven fabric, the firmness of the connection can be further improved and the conductivity can be improved.

[0010] In any embodiment, the conductive carbon film layer is disposed on both sides of the non-woven fabric layer; and the conductive film layer is disposed on both sides of the two conductive carbon film layers facing away from the non-woven fabric layer. The connection firmness and the conductive performance can be further improved by disposing the conductive carbon film layer on both sides of the non-woven fabric layer; and the conductive film layer is disposed on both sides of the two conductive carbon film layers facing away from the non-woven fabric layer.

[0011] In any embodiment, the thickness of the conductive carbon film layer is 0.1 to 1 μm. When the thickness of the conductive carbon film layer is within this range, the volume space occupied by the conductive carbon film layer can be reduced while improving the conductivity and bonding properties, thereby reducing the impact on the mass ratio of the active material; optionally, the thickness of the conductive carbon film layer is 0.15 to 0.7 μm, which can further reduce the volume space occupied by the conductive carbon film layer while improving the conductivity, thereby reducing the impact on the mass ratio of the active material; and / or,

[0012] The thickness of the non-woven fabric is 3 to 20 μm. When the thickness of the non-woven fabric is within this range, the strength of the current collector can be improved while reducing the influence on the mass ratio of the active material. Optionally, the thickness of the non-woven fabric is 5 to 15 μm, which can further improve the strength of the current collector while reducing the influence on the mass ratio of the active material. And / or,

[0013] The thickness of the conductive film layer is 2 to 16 μm. Within this range, the conductive film layer can improve the conductive performance while reducing the volume space occupied by the conductive film layer, thereby reducing the impact on the mass ratio of the active material. Optionally, the thickness of the conductive film layer is 3 to 10 μm, which can further improve the conductive performance while reducing the volume space occupied by the conductive film layer, thereby reducing the impact on the mass ratio of the active material.

[0014] In any embodiment, the thickness ratio of the non-woven fabric layer to the conductive carbon film layer and the conductive film layer is 1: (0.05-0.2): (0.5-1). The thickness ratio of the non-woven fabric layer to the conductive carbon film layer and the conductive film layer is within this range, which can provide suitable collector conductivity, mechanical strength and structural stability, while improving the wettability of the collector and reducing the impact on the mass proportion of the active material; optionally, the thickness ratio of the non-woven fabric layer to the conductive carbon film layer and the conductive film layer is 1: (0.06-0.1): (0.6-0.8), which can further provide suitable collector conductivity, mechanical strength and structural stability, while improving the wettability of the collector and reducing the impact on the mass proportion of the active material.

[0015] In any embodiment, the thermal melting temperature of the non-woven fabric is 350 to 500°C. The thermal melting temperature of the non-woven fabric is within this range. The thermal melting temperature of the non-woven fabric is relatively high, which can reduce the risk of failure of the collector due to hot melting of the non-woven fabric when heat is released inside the battery cell, thereby improving the thermal stability of the collector and thus improving the cycle performance of the battery; optionally, the thermal melting temperature of the non-woven fabric material is 380 to 420°C, which can further save costs while improving the thermal stability of the collector when heat is released inside the battery cell and thus improving the cycle performance of the battery.

[0016] In any embodiment, the material of the non-woven fabric includes at least one of polyimide, polyphenylene sulfide and polyetheretherketone. Using at least one of the above non-woven fabrics can provide suitable thermal stability for the current collector, saving costs. When heat is released inside the battery cell, the thermal melting temperature of the non-woven fabric is high, reducing the risk of failure of the current collector after the non-woven fabric is hot-melted, improving the thermal stability of the current collector, and thus improving the cycle performance of the battery.

[0017] In any embodiment, the material of the non-woven fabric includes polyimide, and the weight of the polyimide non-woven fabric is 5 to 30 g / m 2 The weight of the polyimide nonwoven fabric is within this range, which can improve the mechanical strength of the current collector while reducing the impact on the mass ratio of the active material. Optionally, the weight of the polyimide nonwoven fabric is 10-20 g / m 2 , which can further improve the mechanical strength of the current collector while reducing the impact on the mass ratio of the active material; and / or,

[0018] The material of the non-woven fabric includes polyphenylene sulfide, and the weight of the polyphenylene sulfide non-woven fabric is 5 to 35 g / m 2 The weight of the polyphenylene sulfide nonwoven fabric is within this range, which can improve the mechanical strength of the current collector while reducing the impact on the mass ratio of the active material. Optionally, the weight of the polyphenylene sulfide nonwoven fabric is 10 to 25 g / m 2 , which can further improve the mechanical strength of the current collector while reducing the impact on the mass ratio of the active material; and / or,

[0019] The material of the non-woven fabric includes polyetheretherketone, and the weight of the polyetheretherketone non-woven fabric is 5 to 40 g / m 2 The weight of the polyetheretherketone nonwoven fabric is within this range, which can improve the mechanical strength of the current collector while reducing the impact on the mass ratio of the active material. Optionally, the weight of the polyetheretherketone nonwoven fabric is 10 to 30 g / m 2 , which can further improve the mechanical strength of the current collector while reducing the impact on the mass proportion of the active material.

[0020] In any embodiment, the conductive film layer comprises a conductive metal film layer. The conductive metal film layer can improve the conductivity of the conductive film layer, improve the stability of the conductive film layer, and thus improve the cycle performance of the battery.

[0021] In any embodiment, the conductive metal in the conductive metal film layer includes at least one of copper and aluminum. Using at least one of copper and aluminum can reduce costs while improving the conductivity of the conductive film layer, improving the stability of the conductive film layer, and thus improving the cycle performance of the battery.

[0022] In a second aspect, an embodiment of the present application provides a method for preparing a current collector, which is used to prepare the current collector of the first aspect of the present application, comprising the following steps:

[0023] Provide non-woven fabrics;

[0024] forming a conductive carbon film layer on at least one side of the non-woven fabric;

[0025] A conductive film layer is formed on the side of the conductive carbon film layer away from the non-woven fabric.

[0026] By forming a conductive carbon film layer on at least one side of the non-woven fabric, and forming a conductive film layer on the side of the conductive carbon film layer away from the non-woven fabric, a current collector of a non-woven fabric-conductive carbon layer-conductive layer structure can be obtained, so that the non-woven fabric layer is connected to the conductive film layer through the conductive carbon film layer. On the one hand, the non-woven fabric has a porous structure, which can improve the electrolyte wettability of the battery system, shorten the infiltration time, improve the production effect, improve the anode interface problem, and improve the cycle performance of the battery. On the other hand, by arranging a conductive carbon film layer between the non-woven fabric and the conductive film layer, the conductive film layer is connected to the non-woven fabric through the conductive carbon layer, which improves the connection firmness between the conductive film layer and the non-woven fabric, reduces the probability of cracking and demolding, reduces the gap between the conductive film layer and the non-woven fabric, and thus reduces the contact resistance and improves the cycle performance of the battery.

[0027] In any embodiment, the step of forming a conductive carbon film layer on at least one side of the non-woven fabric comprises: forming a graphene layer on at least one side of the non-woven fabric using a laser induction method.

[0028] Forming a graphene layer on at least one side of the non-woven fabric by laser induction can improve the bonding strength between the graphene layer and the non-woven fabric layer and reduce the contact resistance. It should be noted that when the graphene layers are formed on both sides of the non-woven fabric, the bonding strength and contact resistance reduction effects are better.

[0029] In any embodiment, the laser type of the laser induction includes a carbon dioxide laser, and the use of carbon dioxide laser induction can reduce the influence of the laser on the current collector mechanism; and / or,

[0030] The laser power of the laser induction is 10 to 150 W, at which the growth efficiency of graphene can be improved and the firmness of the bonding can be improved. Optionally, the laser power of the laser induction is 50 to 100 W, which can further improve the growth efficiency of graphene and the firmness of the bonding; and / or,

[0031] The frequency of laser induction is 10 to 60 Hz, at which the growth efficiency of graphene can be improved and the firmness of the bonding can be improved; optionally, the frequency of laser induction is 15 to 45 Hz, which can further improve the growth efficiency of graphene and the firmness of the bonding; and / or,

[0032] The laser-induced time interval is 0.1 to 1 s, during which a suitable graphene layer thickness can be provided to improve the firmness of the bonding; optionally, the laser-induced time interval is 0.2 to 0.8 s, which can further provide a suitable graphene layer thickness to improve the firmness of the bonding.

[0033] In a third aspect, an embodiment of the present application provides a pole piece, comprising a current collector according to the first aspect of the present application, or a current collector prepared by the method for preparing the current collector according to the second aspect of the present application.

[0034] In any embodiment, the electrode sheet includes at least one of a positive electrode sheet and a negative electrode sheet.

[0035] In a fourth aspect, an embodiment of the present application provides a battery, comprising the electrode of the third aspect of the present application.

[0036] In any embodiment, the battery comprises a lithium ion battery or a sodium ion battery.

[0037] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising the battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic structural diagram of a current collector according to one embodiment of the present application.

[0039] Figure 2 It is a schematic structural diagram of a current collector according to one embodiment of the present application.

[0040] Figure 3 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0041] Figure 4 yes Figure 3 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0042] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.

[0043] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0044] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0045] Figure 8 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0046] Description of reference numerals:

[0047] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly; 54 current collector; 541 base film; 542 conductive carbon film layer; 543 conductive film layer. DETAILED DESCRIPTION

[0048] The following specifically discloses the embodiments of the current collector, the preparation method of the current collector, the negative electrode sheet, the battery and the electric device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0049] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0052] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0053] Sodium-ion batteries have the advantages of low cost and abundant reserves. The electrolyte has high conductivity, is more stable at low potential, and has a low probability of reaction with the current collector. They have broad application prospects in the fields of energy storage and power batteries. During the charge and discharge process of sodium-ion batteries, sodium ions escape from the positive electrode and embed into the negative electrode. In the process of sodium ions embedding into the negative electrode, it is easy to cause the expansion and deformation of the negative electrode active material, which in turn affects the cycle performance of the battery.

[0054] Therefore, there are endless studies on reducing the volume expansion of negative electrode active materials, for example, the preparation method of low-expansion silicon-carbon current collector for lithium-ion batteries. A three-step method is used to achieve integrated preparation of pore formation and coating. Through this method, the pore former is fully thermally decomposed on the surface of the silicon powder to form pores to achieve a preliminary pore skeleton. The asphalt flows on the surface of the pore skeleton to coat the surface to form a silicon-carbon material with internal porousness and uniform and dense surface coating. The internal porousness formed after carbonization can effectively buffer the volume expansion of silicon. At the same time, the dense surface coating layer can achieve a low specific surface area and improve the interface, so that the capacity, initial efficiency, and power performance of the silicon-carbon negative electrode can be greatly improved. However, this method requires pore formation in advance, and the introduction of the pore former will affect the proportion of active materials in the battery and affect the energy density of the battery.

[0055] Unexpectedly, by connecting the conductive film layer through the conductive carbon film layer in the non-woven fabric layer, the non-woven fabric has a porous structure, which can improve the electrolyte wettability of the battery system, shorten the wetting time, improve the production effect, improve the anode interface problem, and improve the cycle performance of the battery cell.

[0056] Based on this, the present application provides a current collector and a preparation method thereof, a negative electrode sheet, a battery and an electrical device.

[0057] like Figures 1 to 2 As shown, in the first aspect, an embodiment of the present application proposes a current collector 54, comprising a base film 541, a conductive film layer 543 provided on at least one side of the base film 541, and a conductive carbon film layer 542 located between the base film 541 and the conductive film layer 543, wherein the base film 541 includes a non-woven fabric layer.

[0058] Therefore, in the technical solution of the embodiment of the present application, the base film 541 includes a non-woven fabric layer, so that the non-woven fabric layer is connected to the conductive film layer 543 through the conductive carbon film layer 542. On the one hand, the non-woven fabric has a porous structure, which can improve the electrolyte wettability of the battery system, shorten the infiltration time, improve the production effect, improve the anode interface problem, and improve the cycle performance of the battery. On the other hand, by arranging a conductive carbon film layer 542 between the non-woven fabric and the conductive film layer 543, the conductive film layer 543 is connected to the non-woven fabric through the conductive carbon layer, which improves the connection firmness between the conductive film layer 543 and the non-woven fabric, reduces the probability of cracking and demolding, reduces the gap between the conductive film layer 543 and the non-woven fabric, and thus reduces the contact resistance and improves the cycle performance of the battery.

[0059] It should be noted that, in some embodiments of the present application, the conductive carbon film layer 542 may be a conductive film layer 543 that partially contains carbon. In some embodiments of the present application, the conductive carbon film layer 542 may be a conductive film layer 543 that only contains carbon. The present application does not limit this. A conductive carbon film layer 542 is provided on at least one side of the base film 541. In some embodiments of the present application, such as Figure 1 As shown, the conductive carbon film layer 542 may be provided only on one side of the base film 541. In some embodiments of the present application, for example Figure 2 As shown, a conductive carbon film layer 542 may be provided on both sides of the base film 541 .

[0060] In any embodiment, the conductive carbon film layer 542 includes at least one of a graphite layer or a graphene layer. By using at least one of a graphite layer or a graphene layer, the characteristics of graphite and graphene being easy to deposit and connect on the rough surface of the non-woven fabric can be utilized to improve the firmness of the combination of the graphite layer or the graphene layer with the non-woven fabric layer, reduce the pores in the contact cross section, reduce the risk of falling off, and thus reduce the contact resistance and improve the cycle performance of the battery cell. At the same time, graphite and graphene have good electrical conductivity, which can improve the conductivity of the current collector 54. It should be noted that when the conductive carbon film layer 542 is a graphene layer, due to the good growth performance of graphene and the rough and porous fiber structure of the non-woven fabric, the firmness of the connection can be further improved and the conductivity can be improved.

[0061] In any embodiment, the conductive carbon film layer 542 is disposed on both sides of the non-woven fabric layer; and the conductive film layer 543 is disposed on both sides of the two conductive carbon film layers 542 facing away from the non-woven fabric layer. The conductive carbon film layer 542 is disposed on both sides of the non-woven fabric layer; and the conductive film layer 543 is disposed on both sides of the two conductive carbon film layers 542 facing away from the non-woven fabric layer, which can further improve the firmness of the connection and improve the conductivity.

[0062] In any embodiment, the thickness of the conductive carbon film layer 542 is 0.1 to 1 μm. When the thickness of the conductive carbon film layer 542 is within this range, the volume space occupied by the conductive carbon film layer 542 can be reduced while improving the conductivity and bonding properties, thereby reducing the impact on the mass ratio of the active material. The thickness of the conductive carbon film layer 542 can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1.0 μm; optionally, the thickness of the conductive carbon film layer 542 is 0.15 to 0.7 μm, which can further reduce the volume space occupied by the conductive carbon film layer 542 while improving the conductivity, thereby reducing the impact on the mass ratio of the active material; and / or,

[0063] The thickness of the non-woven fabric is 3 to 20 μm. When the thickness of the non-woven fabric is within this range, the strength of the current collector 54 can be improved while reducing the influence on the mass proportion of the active material. The thickness of the non-woven fabric can be 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm or 20 μm. Optionally, the thickness of the non-woven fabric is 5 to 15 μm, which can further improve the strength of the current collector 54 while reducing the influence on the mass proportion of the active material. And / or,

[0064] The thickness of the conductive film layer 543 is 2 to 16 μm. When the thickness of the conductive film layer 543 is within this range, the conductive performance can be improved while reducing the volume space occupied by the conductive film layer 543, thereby reducing the impact on the mass ratio of the active material. The thickness of the conductive film layer 543 may be 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm or 16 μm. Optionally, the thickness of the conductive film layer 543 is 3 to 10 μm, which can further improve the conductive performance while reducing the volume space occupied by the conductive film layer 543, thereby reducing the impact on the mass ratio of the active material.

[0065] In any embodiment, the thickness ratio of the non-woven fabric layer to the conductive carbon film layer 542 and the conductive film layer 543 is 1: (0.05-0.2): (0.5-1). The thickness ratio of the non-woven fabric layer to the conductive carbon film layer 542 and the conductive film layer 543 within this range can provide suitable electrical conductivity, mechanical strength and structural stability of the current collector 54, while improving the wettability of the current collector 54 and reducing the impact on the mass proportion of the active material; optionally, the thickness ratio of the non-woven fabric layer to the conductive carbon film layer 542 and the conductive film layer 543 is 1: (0.06-0.1): (0.6-0.8), which can further provide suitable electrical conductivity, mechanical strength and structural stability of the current collector 54, while improving the wettability of the current collector 54 and reducing the impact on the mass proportion of the active material.

[0066] In any embodiment, the thermal melting temperature of the non-woven fabric is 350-500°C. The thermal melting temperature of the non-woven fabric is within this range. The thermal melting temperature of the non-woven fabric is relatively high. When heat is released inside the battery cell, the risk of failure of the collector caused by hot melting of the non-woven fabric can be reduced, and the thermal stability of the collector can be improved, thereby improving the cycle performance of the battery. The thermal melting temperature of the non-woven fabric can be 350°C, 370°C, 390°C, 400°C, 420°C, 440°C, 450°C, 470°C, 490°C or 500°C; optionally, the thermal melting temperature of the non-woven fabric material is 380-420°C, which can further save costs while improving the thermal stability of the collector 54 when heat is released inside the battery cell, thereby improving the cycle performance of the battery.

[0067] In any embodiment, the material of the non-woven fabric includes at least one of polyimide, polyphenylene sulfide and polyetheretherketone. Using at least one of the above non-woven fabrics can provide suitable thermal stability for the current collector 54, saving costs. When heat is released inside the battery cell, the thermal melting temperature of the non-woven fabric is high, reducing the risk of failure of the current collector after the non-woven fabric is hot-melted, improving the thermal stability of the current collector 54, and thus improving the cycle performance of the battery.

[0068] In any embodiment, the material of the non-woven fabric includes polyimide, and the weight of the polyimide non-woven fabric is 5 to 30 g / m 2 The weight of the polyimide nonwoven fabric is within this range, which can improve the mechanical strength of the current collector 54 while reducing the impact on the mass ratio of the active material. The weight of the polyimide nonwoven fabric can be 5g / m 2 , 10g / m 2 , 15g / m 2 , 20g / m 2 , 25g / m 2 or 30g / m 2 Optionally, the polyimide nonwoven fabric has a gram weight of 10 to 20 g / m 2 , which can further improve the mechanical strength of the current collector 54 while reducing the impact on the mass ratio of the active material.

[0069] The material of the non-woven fabric includes polyphenylene sulfide, and the weight of the polyphenylene sulfide non-woven fabric is 5 to 35 g / m 2 The weight of the polyphenylene sulfide nonwoven fabric is within this range, which can improve the mechanical strength of the current collector 54 while reducing the impact on the mass ratio of the active material. The weight of the polyphenylene sulfide nonwoven fabric can be 5g / m 2 , 10g / m 2 , 15g / m 2 , 20g / m 2 , 25g / m2 , 30g / m 2 or 35g / m 2 Optionally, the polyphenylene sulfide nonwoven fabric has a gram weight of 10 to 25 g / m 2 , which can further improve the mechanical strength of the current collector 54 while reducing the impact on the mass ratio of the active material.

[0070] The material of the non-woven fabric includes polyetheretherketone, and the weight of the polyetheretherketone non-woven fabric is 5 to 40 g / m 2 The weight of the polyetheretherketone nonwoven fabric is within this range, which can improve the mechanical strength of the current collector 54 while reducing the impact on the mass ratio of the active material. The weight of the polyetheretherketone nonwoven fabric can be 5g / m 2 , 10g / m 2 , 15g / m 2 , 20g / m 2 , 25g / m 2 , 30g / m 2 , 35g / m 2 or 40g / m 2 Optionally, the polyetheretherketone nonwoven fabric has a gram weight of 10 to 30 g / m 2 , which can further improve the mechanical strength of the current collector 54 while reducing the impact on the mass ratio of the active material.

[0071] In any embodiment, the conductive film layer 543 includes a conductive metal film layer. The conductive metal film layer can improve the conductivity of the conductive film layer 543, improve the stability of the conductive film layer 543, and further improve the cycle performance of the battery.

[0072] In any embodiment, the conductive metal in the conductive metal film layer includes at least one of copper and aluminum. Using at least one of copper and aluminum can reduce costs while improving the conductivity of the conductive film layer 543, improving the stability of the conductive film layer 543, and thus improving the cycle performance of the battery.

[0073] In a second aspect, an embodiment of the present application provides a method for preparing a current collector, which is used to prepare the current collector of the first aspect of the present application, comprising the following steps:

[0074] Provide non-woven fabrics;

[0075] forming a conductive carbon film layer on at least one side of the non-woven fabric;

[0076] A conductive film layer is formed on the side of the conductive carbon film layer away from the non-woven fabric.

[0077] By forming a conductive carbon film layer on at least one side of the non-woven fabric, and forming a conductive film layer on the side of the conductive carbon film layer away from the non-woven fabric, a current collector of a non-woven fabric-conductive carbon layer-conductive layer structure can be obtained, so that the non-woven fabric layer is connected to the conductive film layer through the conductive carbon film layer. On the one hand, the non-woven fabric has a porous structure, which can improve the electrolyte wettability of the battery system, shorten the infiltration time, improve the production effect, improve the anode interface problem, and improve the cycle performance of the battery. On the other hand, by arranging a conductive carbon film layer between the non-woven fabric and the conductive film layer, the conductive film layer is connected to the non-woven fabric through the conductive carbon layer, which improves the connection firmness between the conductive film layer and the non-woven fabric, reduces the probability of cracking and demolding, reduces the gap between the conductive film layer and the non-woven fabric, and thus reduces the contact resistance and improves the cycle performance of the battery.

[0078] In any embodiment, the step of forming a conductive carbon film layer on at least one side of the non-woven fabric comprises: forming a graphene layer on at least one side of the non-woven fabric using a laser induction method.

[0079] Forming a graphene layer on at least one side of the non-woven fabric by laser induction can improve the bonding strength between the graphene layer and the non-woven fabric layer and reduce the contact resistance. It should be noted that when the graphene layers are formed on both sides of the non-woven fabric, the bonding strength and contact resistance reduction effects are better.

[0080] In any embodiment, the laser type of the laser induction includes a carbon dioxide laser. The use of carbon dioxide laser induction can reduce the influence of the laser on the current collector mechanism.

[0081] The laser power induced by the laser is 10 to 150 W. At this power, the growth efficiency of graphene can be improved and the firmness of the bonding can be improved. The laser power induced by the laser can be 10 W, 20 W, 30 W, 40 W, 50 W, 60 W, 70 W, 80 W, 90 W, 100 W, 110 W, 120 W, 130 W, 140 W or 150 W. Optionally, the laser power induced by the laser is 50 to 100 W, which can further improve the growth efficiency of graphene and improve the firmness of the bonding.

[0082] The frequency of laser induction is 10 to 60 Hz. At this power, the growth efficiency of graphene can be improved and the firmness of the bonding can be improved. The frequency of laser induction can be 10 Hz, 15 Hz, 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz, 50 Hz, 55 Hz or 60 Hz. Optionally, the frequency of laser induction is 15 to 45 Hz, which can further improve the growth efficiency of graphene and improve the firmness of the bonding.

[0083] The time interval of laser induction is 0.1 to 1 second. During this time, it is convenient to control the number of graphene layers generated, provide a suitable graphene layer thickness, improve the quality of the generated graphene, improve the conductivity and electron migration rate, and generate three-dimensional porous graphene, which can further improve the bonding force of the conductive metal layer. The time interval of laser induction can be 0.1 second, 0.2 second, 0.3 second, 0.4 second, 0.5 second, 0.6 second, 0.7 second, 0.8 second, 0.9 second or 1 second; optionally, the time interval of laser induction is 0.2 to 0.8 second, which can further provide a suitable graphene layer thickness and improve the firmness of bonding.

[0084] It should be noted that the above-mentioned laser-induced laser type, laser-induced laser type, laser-induced frequency and laser-induced time interval can be set simultaneously or separately. When set simultaneously, the thickness of the formed graphene layer is more appropriate and the bonding force is better.

[0085] In a third aspect, an embodiment of the present application provides a pole piece, comprising a current collector according to the first aspect of the present application, or a current collector prepared by the method for preparing the current collector according to the second aspect of the present application.

[0086] In any embodiment, the electrode sheet includes at least one of a positive electrode sheet and a negative electrode sheet.

[0087] In a fourth aspect, an embodiment of the present application provides a battery, comprising the electrode of the third aspect of the present application.

[0088] In any embodiment, the battery comprises a lithium ion battery or a sodium ion battery.

[0089] In any embodiment, the battery comprises a primary battery or a secondary battery.

[0090] In one embodiment of the present application, a secondary battery is provided. Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0091] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode current collector includes the current collector of the first aspect of the present application.

[0092] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0093] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0094] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0095] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0096] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0097] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0098] As an example, the negative electrode current collector includes the current collector of the first aspect of the present application, having two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector.

[0099] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0100] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0101] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0102] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0103] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0104] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0105] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0106] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0107] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0108] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0109] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0110] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0111] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0112] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0113] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0114] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 3 The secondary battery 5 is a square structure as an example.

[0115] In some embodiments, reference Figure 4 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0116] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0117] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0118] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0119] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0120] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0121] In a fifth aspect, an embodiment of the present application provides an electrical device, comprising the battery of the fourth aspect of the present application.

[0122] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0123] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0124] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0125] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0126] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0127] The parameters of the current collectors of Examples 1 to 32 of the present application and Comparative Examples 1 to 2 are according to the parameters in Table 1.

[0128]

[0129]

[0130] Embodiment 33

[0131] A method for preparing a current collector comprises the following steps:

[0132] Provide non-woven fabrics;

[0133] forming a conductive carbon film layer on at least one side of the non-woven fabric;

[0134] A conductive film layer is formed on the side of the conductive carbon film layer away from the non-woven fabric.

[0135] Embodiment 34

[0136] A method for preparing a current collector comprises the following steps:

[0137] Provide non-woven fabrics;

[0138] forming a graphene layer on at least one side of the nonwoven fabric by a laser induction method;

[0139] A conductive film layer is formed on the side of the conductive carbon film layer away from the non-woven fabric.

[0140] Embodiment 35

[0141] A method for preparing a current collector comprises the following steps:

[0142] Provide polyimide nonwoven fabrics;

[0143] Graphene layers were formed on the two sides of the polyimide nonwoven fabric at an interval of 0.5 s using a 80 W, 30 Hz carbon dioxide laser induction method.

[0144] A conductive film layer is formed on the side of the conductive carbon film layer away from the non-woven fabric.

[0145] The current collectors of Examples 1 to 32 and Comparative Examples 1 to 2 are prepared into batteries, which can be prepared by the following method:

[0146] The current collectors of Examples 2 and 4 to 32 and Comparative Examples 1 to 2 were processed as follows:

[0147] Preparation of positive electrode

[0148] The current collectors of Examples 2 and 4 to 32 of the present invention and Comparative Examples 1 to 2 are used as positive electrode current collectors.

[0149] The positive electrode active material LiNi0.8 Co 0.1 Mn 0.1 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent NMP at a weight ratio of 98.2:1.1:0.7 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode collector, and after drying and cold pressing, a positive electrode sheet is obtained.

[0150] Preparation of negative electrode

[0151] The negative electrode active material artificial graphite, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent carbon black (Super P) are fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 97.0:1.2:1.0:0.8 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode collector, and after drying and cold pressing, a negative electrode sheet is obtained.

[0152] Isolation film

[0153] A porous polyethylene (PE) film is used as the isolation membrane.

[0154] Preparation of battery cells

[0155] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0156] The current collectors of Examples 1 and 3 were treated as negative electrode current collectors as follows:

[0157] Preparation of negative electrode

[0158] The current collectors of Examples 1 and 3 of the present invention are used as negative electrode current collectors. The negative electrode active material artificial graphite, the binder styrene butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC-Na), and the conductive agent carbon black (Super P) are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 97.0:1.2:1.0:0.8 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector, and after drying and cold pressing, a negative electrode sheet is obtained.

[0159] Preparation of positive electrode

[0160] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent NMP at a weight ratio of 98.2:1.1:0.7 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode collector, and after drying and cold pressing, a positive electrode sheet is obtained.

[0161] Isolation film

[0162] A porous polyethylene (PE) film is used as the isolation membrane.

[0163] Preparation of battery cells

[0164] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0165] Perform the following test:

[0166] Performance Testing

[0167] Electrical performance test

[0168] Cycle performance: At 25°C, the lithium-ion battery is charged to 4.25V at 2C constant current, then charged to 0.05C at 4.25V constant voltage, and then discharged to 2.8V at 1C constant current. This is a charge and discharge cycle. Taking the capacity of the first discharge as 100%, calculate the capacity retention rate of the battery after 500 cycles. The capacity retention rate of the battery after 500 cycles (%) = discharge capacity of the 500th cycle / capacity of the first discharge × 100%.

[0169] The statistical experimental results are shown in Table 1.

[0170] As can be seen from Table 1, the base film includes a non-woven fabric layer, so that the non-woven fabric layer is connected to the conductive film layer through the conductive carbon film layer. On the one hand, the non-woven fabric has a porous structure, which can improve the electrolyte wettability of the battery system, shorten the infiltration time, improve the production effect, improve the anode interface problem, and improve the cycle performance of the battery. On the other hand, by arranging a conductive carbon film layer between the non-woven fabric and the conductive film layer, the conductive film layer is connected to the non-woven fabric through the conductive carbon layer, which improves the connection firmness between the conductive film layer and the non-woven fabric, reduces the probability of cracking and demolding, reduces the gap between the conductive film layer and the non-woven fabric, and thus reduces the contact resistance and improves the cycle performance of the battery.

[0171] As can be seen from Examples 2 to 5, the conductive carbon film layer can be provided on only one side of the base film, or on both sides of the base film, both of which can improve the connection firmness between the conductive film layer and the non-woven fabric, reduce the probability of cracking and demolding, reduce the gap between the conductive film layer and the non-woven fabric, and thus reduce the contact resistance and improve the cycle performance of the battery. When both sides are provided, the effect is better.

[0172] It can be seen from Examples 6 to 12 that the thickness of the non-woven fabric is in the range of 3 to 20 μm, which can improve the strength of the current collector while reducing the impact on the mass ratio of the active material.

[0173] It can be seen from Examples 13 to 19 that when the thickness of the conductive carbon film layer is in the range of 0.1 to 1 μm, the conductive properties and bonding properties can be improved while reducing the volume space occupied by the conductive carbon film layer and reducing the impact on the mass ratio of the active material.

[0174] It can be seen from Examples 20 to 26 that the thickness of the conductive film layer is in the range of 2 to 16 μm, which can improve the conductive performance while reducing the volume space occupied by the conductive film layer and reducing the impact on the mass ratio of the active material.

[0175] It can be seen from Examples 27 to 32 that both partial coating and complete coating can improve the mechanical strength of the core material and promote the desolvation of sodium ions when the negative electrode is embedded with sodium, reduce the collapse of the material structure caused by the co-embedding of the solvent, thereby inhibiting the volume expansion of the negative electrode and improving the cycle performance of the battery. The effect is better when it is completely coated.

[0176] It can be seen from Examples 27 to 29 that the thickness ratio of the non-woven fabric layer to the conductive carbon film layer and the conductive film layer is in the range of 1: (0.05-0.2): (0.5-1), which can provide suitable collector conductivity, mechanical strength and structural stability, while improving the wettability of the collector and reducing the impact on the mass ratio of the active material.

[0177] It can be seen from Comparative Examples 1 and 2 that the base film does not use a non-woven fabric layer, the electrode liquid wettability is poor, it is easy to crack and demold, and there is contact resistance, which affects the cycle performance of the battery. If a conductive carbon film layer is not provided between the non-woven fabric layer and the conductive film layer, the bonding is not tight enough, there is contact resistance, and the cycle performance of the battery is affected.

[0178] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A current collector, characterized in that: The invention comprises a base film, a conductive film layer arranged on at least one side of the base film, and a conductive carbon film layer located between the base film and the conductive film layer, wherein the base film comprises a non-woven fabric layer.

2. The current collector according to claim 1, characterized in that The conductive carbon film layer includes at least one of a graphite layer or a graphene layer.

3. The current collector according to claim 1 or 2, characterized in that: The conductive carbon film layer is disposed on both sides of the non-woven fabric layer; A conductive film layer is disposed on the side of the two conductive carbon film layers facing away from the non-woven fabric layer.

4. The current collector according to any one of claims 1 to 3, characterized in that: The thickness of the conductive carbon film layer is 0.1-1 μm; optionally, the thickness of the conductive carbon film layer is 0.15-0.7 μm; and / or, The thickness of the non-woven fabric is 3 to 20 μm; optionally, the thickness of the non-woven fabric is 5 to 15 μm; and / or, The thickness of the conductive film layer is 2 to 16 μm; optionally, the thickness of the conductive film layer is 3 to 10 μm.

5. The current collector according to any one of claims 1 to 4, characterized in that: The thickness ratio of the non-woven fabric layer to the conductive carbon film layer and the conductive film layer is 1: (0.05-0.2): (0.5-1); optionally, the thickness ratio of the non-woven fabric layer to the conductive carbon film layer and the conductive film layer is 1: (0.06-0.1): (0.6-0.8).

6. The current collector according to any one of claims 1 to 5, characterized in that: The thermal melting temperature of the non-woven fabric is 350-500°C; optionally, the thermal melting temperature of the material of the non-woven fabric is 380-420°C.

7. The current collector according to claim 6, characterized in that The material of the non-woven fabric includes at least one of polyimide, polyphenylene sulfide and polyetheretherketone.

8. The current collector according to any one of claims 7, characterized in that: The material of the non-woven fabric includes polyimide, and the weight of the polyimide non-woven fabric is 5 to 30 g / m 2 Optionally, the polyimide nonwoven fabric has a gram weight of 10 to 20 g / m 2 and / or, The material of the non-woven fabric includes polyphenylene sulfide, and the weight of the polyphenylene sulfide non-woven fabric is 5 to 35 g / m 2 Optionally, the polyphenylene sulfide nonwoven fabric has a gram weight of 10 to 25 g / m 2 and / or, The material of the non-woven fabric includes polyetheretherketone, and the weight of the polyetheretherketone non-woven fabric is 5 to 40 g / m 2 Optionally, the polyetheretherketone nonwoven fabric has a gram weight of 10 to 30 g / m 2 .

9. The current collector according to any one of claims 1 to 8, characterized in that: The conductive film layer includes a conductive metal film layer.

10. The current collector according to claim 9, characterized in that: The conductive metal in the conductive metal film layer includes at least one of copper and aluminum.

11. A method for preparing a current collector according to any one of claims 1 to 10, characterized in that: The following steps are involved: Provide non-woven fabrics; forming a conductive carbon film layer on at least one side of the non-woven fabric; A conductive film layer is formed on the side of the conductive carbon film layer away from the non-woven fabric.

12. The method for preparing a current collector according to claim 11, characterized in that: The step of forming a conductive carbon film layer on at least one side of the non-woven fabric comprises: A graphene layer is formed on at least one side of the non-woven fabric by using a laser induction method.

13. The method for preparing a current collector according to claim 12, characterized in that: Laser-induced laser types include carbon dioxide lasers; and / or, The laser power of the laser induction is 10 to 150 W, and optionally, the laser power of the laser induction is 50 to 100 W; and / or, The frequency of laser induction is 10 to 60 Hz; optionally, the frequency of laser induction is 15 to 45 Hz; and / or, The time interval of laser induction is 0.1 to 1 s; optionally, the time interval of laser induction is 0.2 to 0.8 s.

14. A pole piece, characterized in that: A current collector prepared by the current collector according to any one of claims 1 to 10 or the current collector preparation method according to any one of claims 11 to 13.

15. A battery, characterized in that: Comprising the pole piece as claimed in claim 14.

16. The battery according to claim 15, characterized in that Including lithium-ion batteries or sodium-ion batteries.

17. An electrical device, characterized in that: Comprising a battery as claimed in claim 15 or 16.